2015
DOI: 10.5539/ies.v8n11p162
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Pre-University Students’ Mathematics Test Anxiety and Numerical Anxiety on Mathematics Achievement

Abstract: <p class="apa">This study examines the relationship between mathematics test anxiety and numerical anxiety on students’ mathematics achievement. 140 pre-university students who studied at one of the institutes of higher learning were being investigated. Gender issue pertaining to mathematics anxieties was being addressed besides investigating the magnitude of the variables for mathematics test anxiety and numerical anxiety. The data revealed that there was a positive correlation between mathematics test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
1
10
0
2
Order By: Relevance
“…Salah satu definisi terkait dengan mathematics test anxiety mengatakan bahwa dimensi ini mengacu pada kejadian sehari-hari dengan situasi kongkrit yang membutuhkan beberapa bentuk manipulasi angka seperti penambahan dan perkalian (Rounds & Hendel, 1980). Indikator dari dimensi ini mengatakan bahwa perasaan cemas akan muncul ketika seseorang dihadapkan dengan tes Matematika (Seng, 2015). Dengan kata lain melalui dimensi ini dapat dilihat bahwa subyek dalam penelitian mempunyai tingkatan kecemasan Matematika yang tinggi ketika dihadapkan dengan ujian Matematika.…”
Section: Mathematics Test Anxietyunclassified
“…Salah satu definisi terkait dengan mathematics test anxiety mengatakan bahwa dimensi ini mengacu pada kejadian sehari-hari dengan situasi kongkrit yang membutuhkan beberapa bentuk manipulasi angka seperti penambahan dan perkalian (Rounds & Hendel, 1980). Indikator dari dimensi ini mengatakan bahwa perasaan cemas akan muncul ketika seseorang dihadapkan dengan tes Matematika (Seng, 2015). Dengan kata lain melalui dimensi ini dapat dilihat bahwa subyek dalam penelitian mempunyai tingkatan kecemasan Matematika yang tinggi ketika dihadapkan dengan ujian Matematika.…”
Section: Mathematics Test Anxietyunclassified
“…Several authors [13][14][15] point out that anxiety about mathematics is manifested frequently in upper-secondary students, leading us to think that it is not alien to students of the economic disciplines. In the results obtained by [16], it was identified that anxiety about mathematics is inherent to the construct of the attitude toward this subject and therefore impacts performance in learning about issues related to economics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…El fenómeno de la ansiedad hacia las matemáticas se manifiesta con frecuencia en el alumnado de universitarios, no es de extrañar que también esté presente en los estudiantes de economía (Seng, 2015). La relación entre la economía y las matemáticas se ha venido manifestando desde el siglo XVIII, su campo de reflexión ha sido cuantitativo dada la pretensión de la elaboración de conocimiento objetivo sobre los fenómenos económicos así como la construcción de información abstracta a partir de datos empíricos propios del quehacer matemático (Benetti, 2018).…”
Section: Revisión De La Literaturaunclassified